2017
DOI: 10.1371/journal.pone.0174053
|View full text |Cite
|
Sign up to set email alerts
|

External validity of randomized controlled trials in older adults, a systematic review

Abstract: BackgroundTo critically assess the external validity of randomized controlled trials (RCTs) it is important to know what older adults have been enrolled in the trials. The aim of this systematic review is to study what proportion of trials specifically designed for older patients report on somatic status, physical and mental functioning, social environment and frailty in the patient characteristics.MethodsPubMed was searched for articles published in 2012 and only RCTs were included. Articles were further excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 14 publications
0
40
0
3
Order By: Relevance
“…Because of this strict patient selection in RCTs, the patient population may differ in daily clinical practice. Thus, treatment effect in clinical practice may be different from an RCT‐based treatment effect …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this strict patient selection in RCTs, the patient population may differ in daily clinical practice. Thus, treatment effect in clinical practice may be different from an RCT‐based treatment effect …”
Section: Introductionmentioning
confidence: 99%
“…Thus, treatment effect in clinical practice may be different from an RCT-based treatment effect. 3,5,6 Observational studies without patient selection, although lower on the GRADE scale, are closer to clinical practice. In particular, after the introduction of electronic medical records, more and more scientists and decision makers are arguing for the use of observational studies in addition to RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinically relevant, the subject of statin discontinuation in older adults gets little attention in current international cardiovascular prevention guidelines, resulting in a lack of clear guidance for physicians reconsidering statin treatment in older adults with complex health problems. In this population, physicians will have to decide to continue or discontinue statins based on personal judgment, since evidence concerning the optimal duration of statin treatment in older frail adults or adults with multimorbidity is currently lacking . Grants to develop randomized trials on deprescribing in older adults will probably result in more evidence for deprescribing.…”
Section: Discussionmentioning
confidence: 99%
“…But evidence on how to treat older patients is lacking, as older patients are often excluded from clinical studies and specific frailty syndromes are not reported, even in trials designed specifically for this patient group. [4,5].…”
Section: Editorialmentioning
confidence: 99%